Specification for interchangeability and safety of a standardized luminaire supporting coupler (BSI, 1988)
Lighting equipment, Luminaires, Electric connectors, Electric plugs, Electric sockets, Ceiling roses, Interchangeability, Dimensions, Electrical safety, Rated current, Rated voltage, Load capacity, Design